2005
DOI: 10.2202/1940-1639.1468
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Effectiveness of a Collegiate Character Education Program

Abstract: In this cross-sectional study of a Character Development program, the Defining Issues Test II was administered to 600 college students to measure moral reasoning, 3% of the seniors were interviewed, along with examining grades and disciplinary referrals. Evidence revealed that a comprehensive character development program has a positive effect on moral reasoning development, academic achievement, and behavior of college students. In this cross-sectional study of a Character Development program, the Defining Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Given all this, and as we will see in relationships with non‐Greeks as well, the gentle way to talk about pledging is that it teaches situational ethics. A harsher reading would be that in the context of college campuses—where students live by but are also in the process of developing personal and communal codes of ethics and conduct (Harris 1916), and where they are taught those ethics in large part through role modeling (Larson and Martin 2005)—BGLOs that pledge simultaneously and unavoidably also teach students to lie and to do so with a sense of righteousness that recasts purposeful deception as the brave defense of traditional values. Which of these interpretations is more apt is, of course, up to the reader to decide.…”
Section: Part III Pledging Verse Hazingmentioning
confidence: 99%
“…Given all this, and as we will see in relationships with non‐Greeks as well, the gentle way to talk about pledging is that it teaches situational ethics. A harsher reading would be that in the context of college campuses—where students live by but are also in the process of developing personal and communal codes of ethics and conduct (Harris 1916), and where they are taught those ethics in large part through role modeling (Larson and Martin 2005)—BGLOs that pledge simultaneously and unavoidably also teach students to lie and to do so with a sense of righteousness that recasts purposeful deception as the brave defense of traditional values. Which of these interpretations is more apt is, of course, up to the reader to decide.…”
Section: Part III Pledging Verse Hazingmentioning
confidence: 99%
“…Character development can be enhanced by participating in diverse educationally purposeful activities (Kuh & Umbach, 2004), viewing character development as an outcome of all the learning processes in a university (Cole, 2004) is of paramount importance in promoting positive development of character for undergraduate students. Successful cases, for instance, the institutions of Lamb et al (2022) and Larson and Martin (2009), demonstrated that with inputs of efforts and employment of effective strategies educators were able to bring about growth in character development in university students.…”
Section: Introductionmentioning
confidence: 99%